1994
DOI: 10.1007/s001250050136
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of blood glucose control in IDDM patients retards the progression of morphological changes in early diabetic nephropathy

Abstract: SummaryWe investigated in a randomized, prospective study the influence of improved blood glucose control during 2-3 years in young insulin-dependent diabetic (IDDM) patients with microalbuminuria, which is indicative of early nephropathy. Patients were randomized either to intensive treatment by continuous subcutaneous insulin infusion (CSII) (n = 9) or CT (n = 9). Kidney biopsies were taken at baseline and after 26-34months. End points were structural changes in the glomeruli. Sensitive, quantitative, morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
4
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 36 publications
6
96
4
5
Order By: Relevance
“…Other studies of renal biopsies suggest that levels of urine albumin excretion below the cutoff for MA increase concomitantly with histological changes in renal morphology that are compatible with early diabetic renal injury (15,16). These data, together with our study, suggest that the rate of change of the ACR is a biochemical estimate of the rate of renal morphological changes related to diabetic nephropathy.…”
Section: Schultz and Associatessupporting
confidence: 79%
“…Other studies of renal biopsies suggest that levels of urine albumin excretion below the cutoff for MA increase concomitantly with histological changes in renal morphology that are compatible with early diabetic renal injury (15,16). These data, together with our study, suggest that the rate of change of the ACR is a biochemical estimate of the rate of renal morphological changes related to diabetic nephropathy.…”
Section: Schultz and Associatessupporting
confidence: 79%
“…In previous studies not using RAAS-blocking treatment, an annual increase in UAER of 5-70% in type 1 diabetic patients with microalbuminuria has been reported [4,5,[7][8][9][10]. In contrast, we found an overall decrease in UAER after the introduction of RAAS-blocking treatment.…”
Section: Discussioncontrasting
confidence: 52%
“…Subsequently, multiple trials have looked at progression rates from micro-to macroalbuminuria and reported progression rates ranging from 5.6 to 30%/year [5][6][7][8][9][10]. Intervention trials have demonstrated that ACEIs reduce the progression from micro-to macroalbuminuria and preserve GFR in type 1 diabetic patients [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs can also increase extracellular matrix and mesangial cell proliferation (Ziyadeh 1993). The diabetic glomerular lesions include structural and functional changes in glomerular filtration membrane barriers, such as thickening of the glomerular basement membrane (GBM) and loss of podocytes (Bangstad et al 1994, Wolf et al 2005, resulting in increased protein excretion. In fact, tubular lesions have been found in diabetics even when the urinary albumin excretion rate is within a normal range.…”
Section: Introductionmentioning
confidence: 99%